Fluxes of nitrous oxide, methane and carbon dioxide on a cultivated peat soil in northern Finland - Hannukkala, Antti; Esala, Martti; Syväsalo, Eija; Regina, Kristiina (it, 2002)
v ok LAP. Yksikön huom.: mkf